Procyclical Labor Productivity and Competing Theories of the Business Cycle: Some Evidence from Interwar U.S. Manufacturing Industries - Bernanke, Ben S.; Parkinson, Martin L. (Journal of Political Economy, 1991)
We study the phenomenon of short-run increasing returns to labor (SRIRL) in a sample of 10 interwar U.S. manufacturing industries. Our main findings are that SRIRL was common in the interwar period and that the pattern of SRIRL across industries was similar to that observed in the postwar period. We argue that, since presumably the Depression was not caused by technical regress, these findings are inconsistent with the claim of real business cycle theorists that SRIRL is in general due to procyclical technical shocks. We propose tests for discriminating between two other leading explanations of SRIRL but find that our conclusions differ by industry.